PENGARUH INVESTMENT OPPORTUNITY SET DAN CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN (Students' Journal of Accounting and Banking, 2013)
This is research study that examined the effect of invesment opportunity set and corporate governance on firm value. Invesment opportunity set proxy which is most valid as a proxy for growth is the price earning ratio and capital expenditures to book value of asset ratio. There are four Corporate Governance mekanism s are used which aim to reduce the agency conflict, namely the audit commitee, independent commissioners, managerial ownership, and institutional ownership.Sample used in this research are all manufacturing companies listed on the BEI in 2009-2011 by 231 sample firm, using purposive sampling method. Corporate data and then tested with normality, multicolinearity, heterocedastisity, and autocorrelation. Further analysis of the use of multiple regression researchers to explain the relationship between these variabels.The result is the price earning ratio, the audit commitee, independent commissioners has positive and not significant effect on firm value, for variable capital expenditures to book value of asset ratio and managerial ownership negative and not significant effect on firm value, while variable institutional ownership positive and significant effect on the firm value.Keywords: the price earning ratio, capital expenditures to book value of asset ratio, the audit commitee, independent commissioners, managerial ownership, and institutional ownership.